2015
DOI: 10.3917/spub.146.0889
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs associés aux accidents de la route dans la ville de Lubumbashi

Abstract: There is an urgent need for accurate information on the rules of the road for drivers and road users to reduce the mortality and morbidity due to road accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
3
8
2
1
Order By: Relevance
“…In Lubumbashi, in 10.18% of cases the crashes were fatal. These results are higher than those found in 2011 and 2012 [7] in the same city where the proportions of fatal crashes were 6.4% in 2011 and 4.73% in 2012.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…In Lubumbashi, in 10.18% of cases the crashes were fatal. These results are higher than those found in 2011 and 2012 [7] in the same city where the proportions of fatal crashes were 6.4% in 2011 and 4.73% in 2012.…”
Section: Discussioncontrasting
confidence: 71%
“…It was also observed that January experienced a higher number of road crashes (9.2%) followed by that of October (9.1%) than the other months. January is the main holiday period in the Democratic Republic of the Congo (January the 1st: conducted in Lubumbashi between 2011 and 2012 found a peak for the two series in November [7]. Kafando found results in Burkina Faso similar to those of the study by Ilunga et al [9].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…ese head injuries are often secondary to road traffic accidents, which are due to the lack of safety measures (lack of traffic control, absence of seatbelt, or helmet for motorcyclists, etc.) [23]. Sometimes they result from work or home accidents or violent sports [4].…”
Section: Discussionmentioning
confidence: 99%